2010
DOI: 10.1016/j.stem.2010.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Sca-1-Positive Skeletal Stem Cell Recruitment by Alendronate Blunts the Anabolic Effects of Parathyroid Hormone on Bone Remodeling

Abstract: SUMMARY The anabolic effects of parathyroid hormone (PTH) on bone formation are impaired by concurrent use of anti-resorptive drugs. We found that the release of active transforming growth factor (TGF)-β1 during osteoclastic bone resorption is inhibited by alendronate. We showed that mouse Sca-1-positive (Sca-1+) bone marrow stromal cells are a skeletal stem cell subset, which are recruited to bone remodeling sites by active TGF-β1 in response to bone resorption. Alendronate inhibits the release of active TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 42 publications
4
99
0
Order By: Relevance
“…Alendronate, a potent inhibitor of bone turnover, is widely used for treatment of high-turnover bone disease, such as postmenopausal osteoporosis. However, it has been recognized clinically that inhibition of osteoclastic function by alendronate blunts the anabolic action of PTH (4), and the underlying mechanism is beginning to be understood (21). We found that along with a reduction in bone turnover markers after treatment with alendronate (Supplemental Figure 8), Cthrc1 expression in bone was substantially reduced, in contrast to the increased expression of Ctsk and Calcr ( Figure 8B).…”
Section: Coupling Function In Vivomentioning
confidence: 69%
“…Alendronate, a potent inhibitor of bone turnover, is widely used for treatment of high-turnover bone disease, such as postmenopausal osteoporosis. However, it has been recognized clinically that inhibition of osteoclastic function by alendronate blunts the anabolic action of PTH (4), and the underlying mechanism is beginning to be understood (21). We found that along with a reduction in bone turnover markers after treatment with alendronate (Supplemental Figure 8), Cthrc1 expression in bone was substantially reduced, in contrast to the increased expression of Ctsk and Calcr ( Figure 8B).…”
Section: Coupling Function In Vivomentioning
confidence: 69%
“…[7][8][9][10]15,[34][35][36][37] As osteoblast precursors/ osteoblasts express membrane-bounded FASL and osteoclasts express FAS, 23,29 osteoblast-osteoclast contact is very likely to happen during the bone remodeling process. Thus, it is reasonable to assume that osteoblast lineage cells are capable of inducing osteoclast apoptosis to serve as an alternative mechanism to govern osteoclast activity.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate supply of osteoblasts from their stem cells, bone marrow MSCs, is critical for bone formation as osteoblasts are non-replicative (7). Particularly, bone remodeling is temporally and spatially controlled and occurs continuously throughout the lifespan to maintain bone mass and architecture (5,7,20,27,(29)(30). During bone resorption by osteoclasts, multiple growth factors and cytokines are acvitated and released from the bone matrix to recruit MSCs and induce differentiation into mature osteoblasts in coupling bone formation with resorption (5,20,29,(31)(32).…”
Section: Discussionmentioning
confidence: 99%